2014
DOI: 10.1159/000365817
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pulmonary Embolism: Conventional Ventilation/Perfusion SPECT Is Superior to the Combination of Perfusion SPECT and Nonenhanced CT

Abstract: Background: Ventilation/perfusion single-emission photon CT (V/P-SPECT) is widely used to detect pulmonary embolism (PE). Any pathological deficit on P-SPECT with a corresponding unremarkable V-SPECT is considered an embolism. This means that a deficit on P-SPECT with a corresponding deficit on the ventilation scan correlates with other lung pathologies such as pneumonia, bullous emphysema or tumor. In principle, it is possible to identify any of these lung pathologies on nonenhanced chest CT and so this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 13 publications
(20 reference statements)
2
36
3
2
Order By: Relevance
“…This is especially advantageous when CTPA and routine V/Q scans are indeterminate/ nondiagnostic. Some authors have reported that V/Q SPECT or V/Q SPECT/CT is superior to Q SPECT/CT alone in diagnosing PE [34,35]. In some scenarios, adding V SPECT would be helpful for more accurate diagnosis: for example, asthma exacerbations, hypoxic vasoconstrictive responses to reduced ventilation and some obstructive airway diseases can show perfusion defects without CT abnormalities and may cause a false-positive diagnosis of PE on Q SPECT/CT.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially advantageous when CTPA and routine V/Q scans are indeterminate/ nondiagnostic. Some authors have reported that V/Q SPECT or V/Q SPECT/CT is superior to Q SPECT/CT alone in diagnosing PE [34,35]. In some scenarios, adding V SPECT would be helpful for more accurate diagnosis: for example, asthma exacerbations, hypoxic vasoconstrictive responses to reduced ventilation and some obstructive airway diseases can show perfusion defects without CT abnormalities and may cause a false-positive diagnosis of PE on Q SPECT/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Main cause of challenges consists in similarity of clinical presentation of CAP and other diseases manifesting with development of infiltrative processes in the lungs (malignant neoplasms, infiltrative pulmonary tuberculosis, pulmonary embolism, etc.) [3][4][5][6]. The process for developing a differential diagnosis between CAP and peripheral lung cancer is associated with particular difficulties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, radionuclide methods of study are of special interest for clinicians because they allow for evaluating not only anatomical structures, but also functional features of the pathological process in respiratory organs [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations